Implementation of Legal Mathematics in Case Resolution Corruption Crime in Indonesia (Case Study of the Harvey Mouis Case at the Central Jakarta Corruption Court) - Antonius Maria Laot Kian (Journal of Legal and Cultural Analytics, 2025)
The purpose of writing this scientific article is to find out and analyze the implementation of legal mathematics in resolving criminal acts of corruption in Indonesia. This article is motivated by the many decisions of the panel of judges which impose varying lengths of sentences from one judge to another, so this raises questions among the public regarding the consistency and legal certainty in imposing sentences for perpetrators of criminal acts of corruption in Indonesia. Harvey Mouis' decision in a corruption case further strengthens the public's suspicions about the Panel of Judges who decided the case, that this decision did not provide justice considering that the punishment given was deemed not commensurate with the losses caused to the state. The results of this research show that differences in judges' decisions regarding the length of punishment in corruption cases are due to the absence of standard guidelines regarding the length of the sentence which are adjusted to the amount of loss caused to the state. What exists so far is only the minimum and maximum punishment limits without paying attention in detail to specific losses. Therefore, in resolving cases of criminal acts of corruption, legal mathematics is required so that judges can increase transparency and accountability in the decision-making process, as well as minimize the occurrence of criminal disparities that often occur in cases of criminal acts of corruption in Indonesia.